2020
DOI: 10.1002/hyp.13715
|View full text |Cite
|
Sign up to set email alerts
|

Change in low flows due to catchment management dynamics—Application of a comparative modelling approach

Abstract: Understanding the natural low flow of a catchment is critical for effective water management policy in semi-arid and arid lands. The Geba catchment in Ethiopia, forming the headwaters of Tekeze-Atbara basin was known for its severe land degradation before the recent large scale Soil and Water conservation (SWC) programs. Such interventions can modify the hydrological processes by changing the partitioning of the incoming rainfall on the land surface. However, the literature lacks studies to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…A study by Tesfaye & Walker [ 29 ] and Araya et al [ 8 ] verified that crop water stress and crop failure were caused by the mismatches of crop growing period with the seasonal rainy period. Similar results were also reported by Hagos et al [ 17 ] and Gebremicael et al [ 30 ] that 80% of the rainfall occurs during the rainy season from July to August.…”
Section: Resultssupporting
confidence: 91%
“…A study by Tesfaye & Walker [ 29 ] and Araya et al [ 8 ] verified that crop water stress and crop failure were caused by the mismatches of crop growing period with the seasonal rainy period. Similar results were also reported by Hagos et al [ 17 ] and Gebremicael et al [ 30 ] that 80% of the rainfall occurs during the rainy season from July to August.…”
Section: Resultssupporting
confidence: 91%
“…To analyze specific anomalies in our results in more detail, the concept of paired‐catchment approach (Folton et al., 2015; Gebremicael et al., 2020; Prosdocimi et al., 2015; Singh & Basu, 2022; Thompson, 2012; Van Loon et al., 2019) is employed. In this analysis, we focus on comparing the differences with and without the anomalous behaviors in the paired catchments rather than changes over time.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, three guidelines are adopted to determine what is acceptable for pairing: (a) adjacent and nearby catchments are preferable and typical in the majority of the paired‐catchment studies as close proximity often helps with the homogeneity of the catchment physical characteristics and climate conditions (Gebremicael et al., 2020; Singh & Basu, 2022). (b) The climate conditions of the paired catchments should be kept consistent (within±10% of annual precipitation and potential evapotranspiration (Van Loon et al., 2019)) and (c) only one potential factor influences flow (i.e., if geology is our variable of interest, catchments with reservoir, high urban percentage (>14%) (Birkinshaw et al., 2021) or significant surface water and groundwater abstractions (>0.2 mm/d) should be excluded to isolate the effect of each of the human activities on event characteristics).…”
Section: Methodsmentioning
confidence: 99%
“…In the central highlands of Ethiopia, a 44% reduction in discharge was observed due to the integrated SWC measures (Yaekob et al, 2020). Gebremicael et al (2020) further confirmed that the drastic reduction in runoff has improved baseflow by 55% due to the intensive SWC works in northern Ethiopia.…”
Section: Resultsmentioning
confidence: 93%
“…In general, the catchment restoration practices have transformed the degraded slopes into greener landscapes (Adimassu et al, 2017; Ayele et al, 2018; Gebremicael et al, 2020; Nyssen et al, 2008; Nyssen et al, 2010; Walraevens et al, 2015; Wolka et al, 2018). These restored watersheds have improved ecosystem services and functions.…”
Section: Introductionmentioning
confidence: 99%